Logistic Business Policy and Strategy: Women's Opportunities and Participation in The Warehouse Industry - Mashudi Mashudi; Luluk Fauziah; Johan Bhimo Sukoco; Anafil Windriya; Vina Septiana Eka Sari (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2021)
Departing from a condition in which the number of women involved in the warehouse sector industry is still low, even though culture in Indonesia does not hinder their involvement, there are opportunities to participate, and the existence or existence of women in this industry is not contradictory, so this study aims to determine how high the level of women's participation in the warehouse sector industry, as well as to find out what factors influence their involvement. This study uses a quantitative approach with an explanatory and survey research format. Data was collected by distributing questionnaires to 70 respondents who were determined purposively. In addition, interviews were also conducted with several respondents as well as documentation and observation techniques. Data processing was carried out using percentage techniques and multiple linear regression techniques with the help of the SPSS (Statistical Program for the Social Science) program The results of this study are as follows: 1) women's participation in the warehouse sector industry is still at a low level; 2) culture, existence and opportunities have an effect either partially or simultaneously on women's participation; 3) while the opportunity variable has the most significant effect on women's participation; 4) there are a small number of other variables that are not involved in this study which also influence women's participation in the warehouse sector industry.